Pengembangan Platform Digital Community-Based Tourism Menggunakan Model System Development Life Cycle untuk Pemberdayaan Masyarakat Wisata Bukit Lawang - Matondang, Sondang; Tumini Sipayung; Andre Pasaribu; Swanra Simare-mare (Universitas Budi Darma, 2025)
This study aims to develop a digital platform based on Community-Based Tourism (CBT) to support community empowerment in the Bukit Lawang tourism area, North Sumatra. Despite its rich natural beauty and cultural values, Bukit Lawang’s tourism potential has not yet provided significant economic benefits to local communities due to low digital literacy and limited online promotion access. The research employs the Research and Development (R&D) method using the System Development Life Cycle (SDLC) model, which includes needs analysis, system design, development, testing, and user evaluation. The results show that the developed CBT digital platform successfully integrates destination information, community-based tourism services, as well as reservation and local product promotion systems. User testing indicates a satisfaction rate of 89%, with a 40% increase in community engagement in tourism promotion and management. Furthermore, the platform strengthens networks among local entrepreneurs, visitors, and tourism managers through an effective digital communication system. This research provides a practical contribution to technology-based community economic empowerment and serves as a replicable model for other sustainable tourism destinations in Indonesia.